2015
DOI: 10.7554/elife.07956.013
|View full text |Cite
|
Sign up to set email alerts
|

Author response: Enhancer additivity and non-additivity are determined by enhancer strength in the Drosophila embryo

Abstract: Metazoan genes are embedded in a rich milieu of regulatory information that often includes multiple enhancers possessing overlapping activities. In this study, we employ quantitative live imaging methods to assess the function of pairs of primary and shadow enhancers in the regulation of key patterning genes-knirps, hunchback, and snail-in developing Drosophila embryos. The knirps enhancers exhibit additive, sometimes even super-additive activities, consistent with classical gene fusion studies. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In addition, enhancer interactions not only help to refine spatial patterns, but can also function to modulate levels of gene expression. For example, some genes, such as kni, sna and Kr, require balanced input from two enhancers (Bothma et al, 2015;Scholes et al, 2019). In the case of kni, two enhancers act in an The proximal (yellow) and distal (gold) enhancers that are bound by Bcd to drive hb gene expression ( pink) are active in similar domains, but the distal enhancer expression, specifically, has a repressive input that acts in a dominant fashion (Perry et al, 2012).…”
Section: Dominant Repression Of Multiple Enhancers Promotes Dynamic Shifts During Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enhancer interactions not only help to refine spatial patterns, but can also function to modulate levels of gene expression. For example, some genes, such as kni, sna and Kr, require balanced input from two enhancers (Bothma et al, 2015;Scholes et al, 2019). In the case of kni, two enhancers act in an The proximal (yellow) and distal (gold) enhancers that are bound by Bcd to drive hb gene expression ( pink) are active in similar domains, but the distal enhancer expression, specifically, has a repressive input that acts in a dominant fashion (Perry et al, 2012).…”
Section: Dominant Repression Of Multiple Enhancers Promotes Dynamic Shifts During Patterningmentioning
confidence: 99%
“…In the case of kni, two enhancers act in an The proximal (yellow) and distal (gold) enhancers that are bound by Bcd to drive hb gene expression ( pink) are active in similar domains, but the distal enhancer expression, specifically, has a repressive input that acts in a dominant fashion (Perry et al, 2012). (B) kni levels (teal) are supported by both proximal and distal enhancers, and each enhancer equally contributes to support kni levels (Bothma et al, 2015). (C) Proximal and distal enhancers at the sna locus act together to regulate levels of expression (brown) in a non-additive (or sub-additive) manner (Bothma et al, 2015;Dunipace et al, 2011).…”
Section: Dominant Repression Of Multiple Enhancers Promotes Dynamic Shifts During Patterningmentioning
confidence: 99%
“…Consistent with previous results [35,36], enhancers appear to be responsible for successive induction of transcriptional bursting because removal of hb shadow enhancer specifically altered the length of transcription period without changing the transcription rate ( Figure 3C and D). Previous transgene assay suggested that hb shadow enhancer is ~2-fold weaker than proximal enhancer [30]. Genome-editing analysis in this study revealed that the deletion of shadow enhancer causes ~2-fold increase in the level of total RNA production ( Figure 3B), suggesting that interaction between P2 promoter and strong proximal enhancer is competitively blocked by distal weak enhancer to downregulate de novo RNA synthesis and facilitate refinement of initial expression domain during nc14.…”
Section: Resultsmentioning
confidence: 52%
“…Gap genes are typically regulated by two redundant enhancers that can produce overlapping patterns in early embryos [27]. While previous transgene assay suggested that redundant enhancers foster robustness of gene expression [28,29] or help to increase transcriptional output [30], it remains unclear if they can simultaneously interact with target promoter. Anterior expression of hb is controlled not only by classical proximal enhancer [24,31], but also by newly-identified distal redundant enhancer, or shadow enhancer [27] ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation